Next of kin - Swayze, Patrick; Baldwin, Adam, 1962-; Hunt, Helen, 1963-; Paxton, Bill.; Neeson, Liam.; Jenning, Michael; Irvin, John.; Lorimar Film Entertainment Company; Warner Bros.; Warner Home Video (Firm) (Burbank, CA : Warner Home Video, 1990)
A cop transplanted from the backwoods of Appalachia to the mean streets of Chicago is involved in a deadly clash that traps him between the mountain code of retribution and the badge he wears.
"670."
"Hi-Fi, Dolby surround, digitally processed."
Rated R.
Closed captioned for the hearing impaired.
Videocassette release of the 1989 motion picture.
Costume designer, Donfeld ; editor, Peter Honess ; production designer, Jack T. Collis ; director of photography, Steven Poster ; music by Jack Nitzsche ; executive producer, Larry De Waay ; written by Michael Jenning ; produced by Les Alexander and Don Enright ; directed by John Irvin.
Keywords: Detective and mystery films; Adventure films; Feature films; Video recordings for the hearing impaired; Police films; Revenge -- Drama